Effect of elderly individuals' perceptions and attitudes toward COVID-19 pandemic on rejecting COVID-19 vaccination - Burcu Beyazgul; İbrahim Koruk; Rüstem Kuzan (Taylor & Francis Group, 2022)
Despite the fact that COVID-19 vaccines serve as an important tool for protection against COVID-19 infection, in individuals aged above 65 years, as well as the entire community, there are significant problems associated with getting vaccinated. The aim of this study is to determine the effect of perceptions and attitudes toward the COVID-19 epidemic in individuals over the age of 65 living in Şanlıurfa, Turkey in 2021, on the situation of having COVID-19 vaccination. The study is designed as a case-control type of research. The study population was comprised of individuals aged 65 years and above located in Şanlıurfa, Turkey. The Case Group consisted of individuals, who rejected the COVID-19 vaccination and the Control Group consisted of individuals who have received the vaccine. The individuals recruited in the Case and Control Groups were selected by means of the snowball sampling method. The study included a total of 240 individuals including 120 in the Case Group and 120 in the Control Group. Rate of vaccine rejection was higher in individuals who believed that the media exaggerated the pandemic, the disease had low contagiousness, the pandemic was a conspiracy, the environmental pollution had no role in the disease, the domestic measures taken against the epidemic were inadequate, the personal hygiene could not protect from disease, and who did not believe that the disease was inevitable [p < 0.05]. Governments have a lot of responsibilities in providing accurate information about vaccination to people and increasing confidence in the health system.